Pemetaan Persebaran Bangunan Sekolah Dasar Negeri (SDN) Berbasis Sistem Informasi Geografis di Tiga Kecamatan Kabupaten Mojokerto - Noviana, Kharisma (Universitas Negeri Surabaya, 2023)
Provision of public elementary school (SDN) is one of equality attempt of educational facilities distribution. Educational facility services of public elementary school (SDN) in the Bangsal, Mojoanyar and Mojosari sub-districts in Mojokerto Regency are currently considered to lack equity. Therefore, it is planned to implement a zoning system. The purpose of this research to assisting the UPT of the local Education Office in planning the implementation of the zoning system for reducing student disparities between schools, preventing excessive student capacity by favorite school, anticipating the closure of non-favorite schools, preventing the incorporation of small school into nearest school. This research uses descriptive methods for mapping and analysis methods to the nearest neighbor for distribution patterns. Nearest neighbours are used to find out whether the distribution pattern is classified as clustered, random, or evenly distributed by looking for the T value from calculations and from ArcGis graphs. In terms of building location, public primary schools in the three sub-districts are recorded as evenly distributed from the two methods, but based on data from the Ministry of Education and Culture for 2023 regarding the availability of educational services, the distribution pattern of the number of teachers and the number of students has not been evenly distributed. Therefore, if the UPT of Education implements the zoning system, it must take more consideration of the distribution of teachers, the number of students, and existing facilities.